2001
DOI: 10.1054/plef.2000.0233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of essential fatty acid deficiency and supplementation with docosahexaenoic acid (DHA; 22:6n-3) on cellular fatty acid compositions and fatty acyl desaturation in a cell culture model

Abstract: 'Effects of essential fatty acid deficiency and supplementation with docosahexaenoic acid (DHA; 22:6n-3) on cellular fatty acid compositions and fatty acyl desaturation in a cell culture model' by Douglas R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…However, it is noticeable that under the present experimental conditions there was not a significant increase in neutral lipids, triacylglicerols or lipid droplets in the cells, indicating that cellular fatty acid composition had been altered without inducing other, possibly adverse, lipid changes. In agreement with our findings, previous studies in different fish cell lines have shown that supplementation with PUFA at low concentration was able to significantly alter fatty acid composition of phospholipids without significantly increasing neutral lipid in these cells (Tocher et al, 1996b;Tocher and Dick, 2001). Surprisingly, DHA + AA supplementation had relatively minor effects on lipid classes compositions in both SN56 and HT22 cell lines.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, it is noticeable that under the present experimental conditions there was not a significant increase in neutral lipids, triacylglicerols or lipid droplets in the cells, indicating that cellular fatty acid composition had been altered without inducing other, possibly adverse, lipid changes. In agreement with our findings, previous studies in different fish cell lines have shown that supplementation with PUFA at low concentration was able to significantly alter fatty acid composition of phospholipids without significantly increasing neutral lipid in these cells (Tocher et al, 1996b;Tocher and Dick, 2001). Surprisingly, DHA + AA supplementation had relatively minor effects on lipid classes compositions in both SN56 and HT22 cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…The side effects of DHA supplementation on fatty acid compositions in HT22 cells were similar to those observed in previous studies, which have shown that supplemental DHA was, in part, retroconverted to eicosapentaenoic acid (EPA) (Youdim et al, 2000;Tocher and Dick, 2001). The process of retroconversion seemed to be important in HT22 cells, where EPA levels increased three-fold higher in PUFA-supplemented HT22 cells compared to control HT22 cells.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The retroconversion of C22 to C20 has been studied in vivo in numerous species: rats, humans, brine shrimp ( Artemia nauplii ), and water flea ( Daphnia magna ) . Many in vitro studies have also reported retroconversion, for instance, in isolated rat liver cells , and human cell lines such as Y79 , bovine aortic endothelial cells , GM‐10 normal fetal human skin fibroblasts, CPA calf pulmonary artery endothelial cells, human umbilical vein endothelium , EPC (epithelial papilloma) cell line from the carp , and 16HBE bronchial epithelial cells . However, to the best of our knowledge the elongation of 22:6n‐3 to 24:6n‐3 has only been reported in studies addressing elongation specifically, and not in the context of partitioning between oxidation and elongation.…”
Section: Discussionmentioning
confidence: 99%
“…The fish oil-enriched caviar paste contained both less alinolenic acid than the ordinary caviar, and more EPA than DHA (Table 2), but probably a part of the increase in EPA also results from an a-linolenic acid conversion. The conversion of EPA to DHA can also go the other way from DHA to EPA (Tocher & Dick, 2001) and it might be preferable with a high EPA content in the food since it can probably slow down this reversible conversion which leads to a decreasing DHA content.…”
Section: Discussionmentioning
confidence: 99%